On Power Consumption Profiles for Data Intensive Workloads in Virtualized Hadoop Clusters - Qureshi, Basit (2017)
IEEE International Conference on Computer Communications (INFOCOM 2017). 1 to 4, May, 2017, Workshop Big Data and Cloud Performance. Atlanta, U.S.A..